Total Anomalous Pulmonary Venous Connection Repair: Single-Center Outcomes in a Lower-Middle Income Region. Issue 4 (July 2022) - Bayya, Praveen Reddy; Varghese, Shruti; Jayashankar, Jessin Puliparambil; Sudhakar, Abish; Balachandran, Rakhi; Kottayil, Brijesh Parayaru; Srimurugan, Balaji; Varma, Praveen Kerala; Neema, Praveen Kumar; Krishna Kumar, R.
Background: The management of total anomalous pulmonary venous connection (TAPVC) in neonates and infants is resource-intensive. We describe early and follow-up outcomes after surgical repair of isolated TAPVC at a single institution in a resource-limited setting. Methods: The data of 316 consecutive patients with isolated TAPVC undergoing repair (January 2010-September 2020) were reviewed. The study setting was a tertiary hospital in southern India that provides subsidized or charitable care. Standard surgical technique was used for repair, circulatory arrest was avoided, and suture-less anastomosis was reserved for small or stenotic pulmonary veins. Surgical and postoperative strategies were directed toward minimizing intensive care unit (ICU) stay. Results: 302 (95.6%) patients were infants and 128 patients (40.5%) were neonates; median weight was 3.3 kg (IQR 2.8-4.0 kg). Obstruction of the TAPVC was seen in 176 patients (56%) and pulmonary hypertension in 278 patients (88%). Seventeen (5.4%) underwent delayed sternal closure. The median postoperative ICU stay was 120 h (IQR 96-192 h), mechanical ventilation was 45 h (IQR 24-82 h), and hospital stay was 13 days (IQR 9-17 days). There were three in-hospital deaths (0.9%). Over a median follow-up period of 53.3 months (IQR 22.9-90.4), pulmonary vein restenosis was seen in 32 patients (10.1%) after a mean of 2.2 months (1-6 months). No perioperative risk factors for restenosis were identified. Conclusions: Using specific perioperative strategies, it is possible to correct TAPVC with excellent surgical outcomes in low-resource environments. Late pulmonary vein restenosis remains an important complication.